2015
DOI: 10.1038/mtna.2015.46
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Native Gastric Mucus on in vivo Hybridization Therapies Directed at Helicobacter pylori

Abstract: Helicobacter pylori infects more than 50% of the worldwide population. It is mostly found deep in the gastric mucus lining of the stomach, being a major cause of peptic ulcers and gastric adenocarcinoma. To face the increasing resistance of H. pylori to antibiotics, antimicrobial nucleic acid mimics are a promising alternative. In particular, locked nucleic acids (LNA)/2'-OMethyl RNA (2'OMe) have shown to specifically target H. pylori, as evidenced by in situ hybridization. The success of in vivo hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Finally, we assessed if the PEGylated lipoplexes could still successfully deliver functional NAMs in H. pylori in the presence of gastric mucus. [24] and [49]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we assessed if the PEGylated lipoplexes could still successfully deliver functional NAMs in H. pylori in the presence of gastric mucus. [24] and [49]).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, they should do so without losing their activity. Indeed, we have recently shown that interactions with gastric mucus can significantly compromise the ability of NAMs to hybridize with Helicobacter pylori (H. pylori) [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helicobacter pylori (Hp) is an important pathogen that colonizes the human gastric mucosa. It is responsible for gastritis, gastroduodenal ulcer disease, gastric adenocarcinoma, mucosa‐associated lymphoid tissue (MALT) lymphoma and may also have a role in some extradigestive conditions . Although infected patients may not have preneoplastic lesions, the progression to cancer is still possible.…”
Section: Introductionmentioning
confidence: 99%
“…It is responsible for gastritis, gastroduodenal ulcer disease, gastric adenocarcinoma, mucosa-associated lymphoid tissue (MALT) lymphoma and may also have a role in some extradigestive conditions. [1][2][3] Although infected patients may not have preneoplastic lesions, the progression to cancer is still possible. Therefore, it is extremely important to eradicate Hp infection.…”
Section: Introductionmentioning
confidence: 99%